(untitled) (Altre Modernità, 2017)
In their thirty-years activity, Marcido Marcidorjs e Famosa Mimosa have been challenging received and ingrained ideas of drama by developing a style capable of reflecting the enormous vacuum of our time, without fearing to be outdated, without having to stick to any agenda but the one dictated by our will to bear witness. "Hamlet" is still able to fascinate us thanks to its uncommon psychological analysis, one which is surprisingly linear, despite - or should we rather say because of? - the depth and density of the knowledge that it conveys. "Hamlet"’s magic works through its poetry, which is like a scan enabling us to sound the inmost recesses of human action. The storyline, therefore, necessarily becomes a mere pre-text of representation, which, in fact, is almost always the case with us, since we are never content with just telling a story.